Immuno-endocrine and metabolic responses to long distance ski racing in world-class male and female cross-country skiers - Ronsen, O.; Borsheim, E.; Bahr, R.; Klarlund Pedersen, B.; Haug, E.; Kjeldsen-Kragh, J.; Hostmark, A. T. (Scandinavian Journal of Medicine & Science in Sports, 2004)
The purpose of this study was to characterize the extent of immune, endocrine, substrate and metabolic changes during a long-distance cross-country ski race in extremely well-trained athletes and evaluate if the blood perturbations would indicate signs of health risk. Ten male (M) and six female (F) national team skiers were investigated as they followed their usual routines of race preparations. Blood samples were drawn before and immediately after a World Cup 50-km M and 30-km F ski race with a mean finish time of 142 and 104 min, respectively. Hemoglobin, electrolytes, and C-reactive protein remained unchanged for both M and F. Serum testosterone remained unchanged in M, but doubled in F. Significant increases were observed in concentrations of granulocytes (F: 5, M: 5), natural killer cells (F: 2, M: 1.5), adrenaline (F: 12, M:10), noradrenaline (F: 7, M:5), growth hormone (F: 30, M: 22), cortisol (F: 1.5, M:2), glucose (F: 2, M:1.5), creatine kinase (F: 2, M:2), uric acid (F: 1.5, M: 1.5) and non-organic phosphate (F:2, M:2), while insulin concentration decreased (F: 0.5, M: 0.8). Free fatty acid (FFA) concentration increased (F:2, M: 3). In conclusion, we observed substantial changes in several immuno-endocrine, substrate and metabolic measurements after long distance cross-country ski racing and suggest that some of these marked changes may reflect the large amount of muscle mass involved during skiing.